The relationship between distributed leadership and family involvement from parents’ perspective - Erol, Yusuf Celal; Turhan, Muhammed (Edam, 2018)
In this study, the relationship between distributed leadership and family involvement in schools from parents’ perspective was examined. The study was carried out with 1,488 secondary school parents in the Elazığ province, Turkey. The Parent Distributed Leadership Perception Scale and Parent Family Involvement Questionnaire were employed. According to the results obtained from the research, parents’ level of involvement in the school, and their level of dealing with their children’s education, increase simultaneously with their positive perceptions on distributed leadership in schools. Furthermore, it can be observed that the distributed leadership perception in schools was a significant predictor of family involvement. Future recommendations were developed for practitioners and researchers based on the results obtained from the research. © 2018 EDAM.
Keywords: Distributed leadership; Family involvement; Parents’ perspective; School-family partnership; Secondary schools